Ubiquitous developments in ambient computing and intelligence human-centered applications - Curran, Kevin 1969- (Information Science Reference, 2011)
"This book provides a comprehensive collection of knowledge in cutting-edge research in fields as diverse as distributed computing, human computer interaction, ubiquitous computing, embedded systems, and other interdisciplinary areas which all contribute to ambient computing and intelligence"--Provided by publisher.